Pragmatism in Online Education – A Case Study Based on the E-learning Practices of Three Adult Trainers - Melpomeni Papadopoulou (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
Flipped classroom is a pedagogical method of blended learning. It alternates distant and face-to-face classes. The idea is simple: students learn the theoretical content of the course in distance via the numerical platform; they then apply it during class exercises and group work. The research question is: which model of flipped classroom would permit appropriate use of digital tools in adults' education? Our qualitative research is based on the analysis of three semi-directive interviews of blended learning adult trainers.